Biografi Sebagai Pintu Masuk Mencermati Peristiwa Remeh Temeh Sehari-Hari Dalam Revolusi Indonesia (1945-1949) di Bali - I. Nyoman Wijaya (Jurnal Sejarah Citra Lekha, 2020)
This study discusses biography as an entry point to talk about trivial everyday events taking place during Indonesia’s physical revolution (1945-1949) in Bali. If in the arena of guerrilla warfare trivial everyday stories can be seen, what about outside the arena? Starting from this central question, this study will attempt to see trivial everyday events in Indonesia’s revolution in Bali, especially events taking place outside the arena of guerrilla warfare. Those events, however, do not stand alone, but they are entwined with Indonesia’s revolution in Bali. Outside the arena of guerilla war, those trivial everyday events can be seen in each stage of Indonesia’s revolution in Bali distributed in various villages. The research results indicate that biographical figures born in the 1930s, aged from 11 to 15-year-old, during the period of guerrilla warfare managed to retell those trivial events. Even though not directly involved in the guerrilla warfare, they were able to provide information about those events, because some of them were actively involved as mail couriers connecting the fighters and their families. Most of the information they provided has not been recorded in the grand narrative of the history of Indonesia’s physical revolution in Bali.